Magnetic Fe3O4/BiOBr for solar-light-responsive photodegradation of tetracycline antibiotic - Detrat, Natthakitta; Matsombat, Kanokwan; Nonthing, Sattra; Panchakeaw, Atchawadee; Dulyasucharit, Ruethaithip; Teerasong, Saowapak; Nanan, Suwat (My University, 2026)
Magnetic Fe3O4/BiOBr photocatalyst was synthesized via an ultrasonic route. It was then applied for detoxification of tetracycline (TC) antibiotic. The prepared BiOBr exhibited Eg of 2.71 eV while the binary Fe3O4/BiOBr showed Eg of 2.04 eV. The Fe3O4/BiOBr photocatalyst displayed lower photoluminescence signal than BiOBr, suggesting the improvement of the electron-hole separation rate after creation of the magnetic Fe3O4/BiOBr photocatalyst. The promising photocatalytic efficiency of 100% was obtained. The corresponding enhanced rate constant of 0.0732 min−1 was achieved. The synthesized Fe3O4/BiOBr exhibited the promising photocatalytic performance and the excellent structural stability after five cycles of use. The superoxide anion radicals are the main active species involved in the degradation of the pollutant. The present paper demonstrates a novel way to fabricate the sunlight-responsive photocatalyst, with magnetic separable property, for decontamination of TC drug in aqueous phase.
Keywords: Antibiotics; Fe3O4/BiOBr; Heterostructure photocatalyst; Magnetic; Sunlight